Gestão de recursos humanos e desempenho hospitalar na Perspectiva da eficiência: um estudo em hospitais brasileiros de pequeno porte - Júnia Marçal Rodrigues (2016)
The main aim of the thesis was to investigate to what extent the Human Resource Management (HRM) contributes to the performance of hospitals, small at the national level in view of efficiency. The literature review addressed the insertion efficiency as one of the possibilities to evaluate hospital performance. and also the prerogatives to measure the contribution of Human Resources (HR) in industrial and health organizations. Quano the methodological approach was applied the technique of data envelopment analysis (DEA) in a sample of 702 hospitals from secondary database coming from censitario survey of 2,777 hospitals in small sizes in Brazil. the central hypothesis that HRM contributes to the efficiency of hospitals, it was confirmed by the results insofar as this was the variable with the greatest need for increased to improve the hospital efficiency as well as the influence of the characteristics regarding size (number of beds), legal institutions and regional distribution.